Gender differences in wage expectations and negotiation - Lukas Kiessling; Pia Pinger; Philipp Seegers; Jan Bergerhoff (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
This paper presents evidence from a large-scale study on gender differences in expected wages before labor market entry. Based on data for over 15,000 students, we document a significant and large gender gap in wage expectations that resembles actual wage differences, prevails across subgroups, and along the entire distribution. Over the life-cycle this gap amounts to roughly half a million Euros. Our findings further suggest that expected wages relate to expected asking and reservation wages and that a difference in plans about "boldness" during prospective wage negotiations pertains to gender difference in expected and actual wages. Given the importance of wage expectations for labor market decisions, household bargaining, and wage setting, our results provide an explanation for persistent gender inequalities.
Keywords: D81; D84; I21; I23; J13; J30; 330; Wage expectations; gender gap; negotiations